2009
DOI: 10.1007/bf03405536
|View full text |Cite
|
Sign up to set email alerts
|

High Health Care Utilization and Costs Associated with Lower Socio-economic Status: Results from a Linked Dataset

Abstract: Objective: The purpose of this paper was to use a linked dataset to compare health care utilization rates and costs between income groups in Saskatoon, Canada. Methods: The Canadian Community Health Survey was linked to hospital, physician and medication data in Saskatoon. Results: Of 3,688 eligible participants, 3,433 agreed to the health survey and data linkage with health records (83.7% overall response). Low-income residents were 27-33% more likely to be hospitalized and 36-45% more likely to receive a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 4 publications
6
56
2
3
Order By: Relevance
“…Given that hospital costs account for the single largest category of total national health costs, we expect that future studies examining total health costs will show similar findings. Fourth, our data did not include measures of health status, socioeconomic status, housing, or mental health comorbidities to permit an analysis of these factors, which have been previously related to frequent hospitalizations and high costs . Fifth, due to resource constraints, we were unable to conduct a longitudinal analysis to examine the extent to which individuals are consistently high users over time.…”
Section: Discussionmentioning
confidence: 99%
“…Given that hospital costs account for the single largest category of total national health costs, we expect that future studies examining total health costs will show similar findings. Fourth, our data did not include measures of health status, socioeconomic status, housing, or mental health comorbidities to permit an analysis of these factors, which have been previously related to frequent hospitalizations and high costs . Fifth, due to resource constraints, we were unable to conduct a longitudinal analysis to examine the extent to which individuals are consistently high users over time.…”
Section: Discussionmentioning
confidence: 99%
“…Low health status is intimately connected to access to social, economic, political and health resources in addition to environmental conditions, rather than being attributable to individual shortcomings or refusal to adopt required health norms. Research suggests that those in lower socioeconomic positions have higher rates of hospitalization compared with the general population (Lemstra et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Low health status is intimately connected to access to social, economic, political and health resources in addition to environmental conditions, rather than being attributable to individual shortcomings or refusal to adopt required health norms. Research suggests that those in lower socioeconomic positions have higher rates of hospitalization compared with the general population (Lemstra et al 2009). Homeless persons have higher rates of service use such as emergency care; this is thought to be in part due to the exacerbation through neglect of minor health conditions, poor living conditions and access barriers to primary healthcare services (Bottomley 2001, Frankish et al 2005, Gundlapalli et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mostly focused on the total cost of care over a defined period (typically a year) and found that lower SES patients have higher costs of care, 9-11 but that much of the impact of SES on resource use is diminished or eliminated entirely after adjusting for comorbidities. 10 Also, previous analyses that have examined the relationship between SES and cost used relatively basic approaches for modeling the relationship between SES and cost and did not examine the impact of SES adjustment on physician relative cost rankings. 9 We examined various model specifications including the inclusion of linear and quadratic interaction terms to allow a flexible relationship between episode type and SES and our analysis specifically focused on a profiling context.…”
Section: Discussionmentioning
confidence: 99%